Validation of existential fulfillment scale in Chinese university students - Chen, Jian; Chen, Xiaoyan; Miao, Chen (Frontiers in Psychology, 2025)
IntroductionThis study aimed to assess the psychometric properties of the Existential Fulfillment Scale (EFS) in a Chinese university student sample, emphasizing the cultural fit of the scale.MethodsA cohort of 1,600 undergraduate students from six universities in Fujian Province completed questionnaires including the EFS, Meaning of Life Questionnaire (MLQ), Index of Well-Being (IWB), and Self-Depression Scale (SDS). We conducted item analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and assessments of criterion-related validity, internal consistency, and test-retest reliability.ResultsThe Chinese EFS consists of two dimensions—self-acceptance and self-breakthrough—across 14 items, reflecting cultural distinctions from the original model by combining the dimensions of self-actualization and self-transcendence. This revised structure aligns with Chinese cultural perspectives on individual growth, where self-actualization often integrates aspects of self-transcendence. The scale showed positive associations with the MLQ and IWB and a negative association with the SDS, supporting the scale’s criterion-related validity. Internal consistency ranged from 0.87 to 0.97, and test-retest reliability ranged from 0.75 to 0.83.DiscussionThese findings indicate that the Chinese EFS is a reliable tool for assessing existential fulfillment among Chinese university students.